Prenatal harmful substances: Thai pregnant women’s experiences - Jatuporn Tantanokit; Nantaporn Sansiriphun; Kasara Sripichyakan; Pimpaporn Klunklin (Belitung Raya Foundation, Indonesia, 2023)
Background: The exposure of unborn babies to harmful substances during prenatal stages can lead to fetal anomalies, emphasizing the significance of pregnant women’s practices in ensuring optimal fetal outcomes. However, there is a lack of understanding regarding this issue from the perspective of pregnant women. Objective: This study aimed to describe the experiences of pregnant women in avoiding harmful substances to their unborn babies. Methods: This study used a qualitative descriptive approach. Data were collected between September 2020 and April 2021 through in-depth interviews with 17 pregnant women purposively selected from two hospitals in southern Thailand. Data were transcribed verbatim and analyzed using thematic analysis. Results: Four themes emerged from the participants’ experiences: 1) understanding of harms, which included substance characteristics, exposure characteristics, body’s protective mechanism, personal experiences, and obtained information; 2) practices for safety, which consisted of food safety, work safety, ambient air safety, and safety in personal/household products; 3) challenges in avoiding harmful substances, which were unrecognition, unavailability of safe substances, discomfort and inconvenience, inevitability, and family traditions; and 4) overcoming the challenges through personal changes, obtaining support, and ensuring a peaceful mind. Conclusion: The findings provide valuable insights into prenatal exposure to harmful substances, which can serve as a basis for developing comprehensive guidelines for best practices. It is crucial for nurses to receive training that enables them to educate pregnant women, enhancing their awareness of important harmful substances and promoting effective methods for maintaining safety in their daily activities. Additionally, nurses can develop interventions to empower pregnant women to overcome challenges by involving significant individuals, particularly family members, in providing support and creating an optimal prenatal environment.